Discharge and floods projected to increase more than precipitation extremes. Issue 11 (1st November 2022) - Quintero, Felipe; Villarini, Gabriele; Prein, Andreas F.; Zhang, Wei; Krajewski, Witold F.
Abstract: Floods claim a high toll in fatalities and economic impacts. Despite their societal relevance, there is much more to learn about the projected changes in discharge and flooding. Here we force an operational hydrologic model over the state of Iowa with high‐resolution convection‐permitting climate‐model precipitation to evaluate the response of 140 watersheds to climate change. At the end of the century, under the most aggressive scenario in terms of fossil fuel use, we show that the transition from snow to rainfall and approximately 30% increase in extreme precipitation rates lead to a doubling of maximum discharge during the spring and extending the flood season into the fall. Total discharge volumes are also expected to increase. Our results suggest that flood projections based on extreme precipitation increases alone substantially underestimate future risk due to the non‐linearity of the hydrologic response explained by long‐term soil moisture memory and its feedbacks with precipitation. This study is one of the first to show floods are increasing due to the prevalence of rain‐on‐snow events, and indeed that discharge might increase more than precipitation. Abstract : The authors examined the projected changes in discharge under the most aggressive scenario in terms of fossil fuel use (RCP8.5) using high‐resolution convection‐permitting climate simulations. Our results show increasing potential flood risk under climate change for Iowa that far exceeds increases from precipitation alone.